Analisis Pola Sebaran Mikro Atol Karang Porites di Pulau Badi Kabupaten Pangkajene dan Kepulauan - Fathuddin Fathuddin; Mesalina Tri Hidayani; Supardi Supardi; Rahmat Januar Noor (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Porites coral is a type of hard coral that forms micro atolls that can survive extreme tides and has a physical function to protect the coast and an ecological function. This study aims to determine the area and pattern distribution of micro atoll, and the types of associated organisms. The research method used is a survey method and is carried out by taking ecological, oceanographic, and biota data found in micro atolls. Data collection was carried out at two stations in the south and north of Badi Island using a quadratic transect placed parallel to the shoreline. Oceanographic conditions around Badi Island meet the sea water quality standards for marine biota. The results showed that the average area of ​​micro atolls found at station one was 0.26 m2 and 0.42 m2 at station two with a Morisita Index was 1, so it can be concluded that the Porites coral micro atolls were randomly distributed. The results of biota identification at both stations showed that the dominant biota in the micro atoll was Tridacna. The conclusion of the study is that there are differences in the area of micro atolls at the two stations but have similarities in distribution patterns and dominant biota.